Effect of Core Competence on Sustainable Competitive Advantages of Batik Banyumas Small and Medium Enterprises - Rahab, R.; Anwar, Nurul; Priyono, Rawuh (Journal of Comparative International Management, 2016)
This study seeks to determine the relationship between firm core competence, competitive advantage and performance of small and medium enterprises based on analysis of data from a survey conducted on 58 owner and manager of small firms of Banyumas batik in Banyumas Region, Central Java, Indonesia. Data was analysed using multiple regression analysis. The results showed that competence in relationship, adaptation and innovation has significantly effect on firms innovativeness. The ability of entrepreneurs to build business network has eased information exchange leading to social relatedness, and thereby contributing to improve the competitive advantage. The results of the study provide new empirical evidence supporting the resources-based view (RBV) theory.